2014
DOI: 10.1001/jamaoto.2014.1936
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Leukotriene Biosynthetic Enzymes in Tonsillar Tissue of Children With Obstructive Sleep Apnea

Abstract: Leukotriene biosynthetic enzymes are expressed in tonsillar lymphocytes, and the previously reported detection of CysLTs in tonsillar tissue from children with OSA may be attributed to endogenous synthesis. Enhanced expression of LTC(4)S is a potential target for pharmacologic interventions in OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
(37 reference statements)
0
11
0
4
Order By: Relevance
“…The initial open-labeled study examining a potential role for anti-leukotriene therapy in pediatric OSA showed encouraging evidence that improvements in both the severity of respiratory disturbance and in the adenoid size could be anticipated in a large proportion of children with mild OSA [60]. We subsequently identified the presence of increased expression and activity of cysteinyl leukotriene receptors within lymphadenoid tissues of OSA children, and these could even be detected in exhaled condensate, serum, circulating white blood cells, or in urine [61][62][63][64][65][66][67][68][69][70]. Two RCTs have been conducted to date and have shown the favorable response to montelukast as a single agent in the treatment of pediatric OSA [71,72].…”
Section: Montelukastmentioning
confidence: 99%
“…The initial open-labeled study examining a potential role for anti-leukotriene therapy in pediatric OSA showed encouraging evidence that improvements in both the severity of respiratory disturbance and in the adenoid size could be anticipated in a large proportion of children with mild OSA [60]. We subsequently identified the presence of increased expression and activity of cysteinyl leukotriene receptors within lymphadenoid tissues of OSA children, and these could even be detected in exhaled condensate, serum, circulating white blood cells, or in urine [61][62][63][64][65][66][67][68][69][70]. Two RCTs have been conducted to date and have shown the favorable response to montelukast as a single agent in the treatment of pediatric OSA [71,72].…”
Section: Montelukastmentioning
confidence: 99%
“…Several studies demonstrated the increased level of cysLTs and expressions of their receptors in adenotonsillar tissues of children with OSA. [2][3][4]16,17 In vitro study, Dayyat et al reported a dose-dependent pattern of LTD 4 in inducing adenotonsillar cell proliferation. 17 This finding supported the findings of in vivo studies which found a positive relationship between urinary LT level and OSA severity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the abundant expressions of leukotrienes (LTs) and their receptors in adenotonsillar tissues and the positive correlation between urinary cysteinyl leukotrienes (cysLTs) levels and OSA severity in children who had OSA. [2][3][4][5][6] These findings lead to the therapeutic use of leukotriene receptor antagonist such as montelukast in children who have mild OSA secondary to ATH. Several studies reported the significant benefits of montelukast in alleviating OSA severity in this particular population.…”
Section: Introductionmentioning
confidence: 99%
“…A familiar predisposition to adenotonsillar hypertrophy and OSAS has been described and it may be attributed to the enhanced expression of leukotriene biosynthetic enzymes in tonsillar tissue and the increased production of cysteinyl leukotrienes which augment the proliferation rate of tonsillar lymphocytes [23][24][25]. Hence, we propose that early recognition of children at risk of adenotonsillar hypertrophy and SDB (e.g.…”
Section: Obese Children With Osas Frequently Have Unfavourable Responmentioning
confidence: 96%